Enhancing Automated Tools: Reporting Bugs with Bug Builder - Chaves, Lennon; Oliveira, Flavia; Tiago, Leonardo (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2024: Anais do IX Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2024)
The detection of issues in software projects is crucial to the quality of the developed product. In particular, a test team within the Institute of Research and Development needs to automate their tests and processes through the creation of tools (software systems) that perform these tasks in an automated manner. Thus, the test team needs to build systems and guarantee that they work adequately. In case of issues, such systems require corrections. In this way, the goal of this work is to share the experience that the test team obtained when creating tools to perform their tasks and report the existing problems in these systems through a tool called Bug Builder. To evaluate Bug Builder, a qualitative review was performed to obtain the test team’s perceptions of the implementation of Bug Builder in the team. Thus, this work aims to contribute to the industry and academia by presenting how the test team acts to ensure the quality of their own developed tools.